Exploring the determinants of digital entrepreneurship using fuzzy cognitive maps - Ladeira, M. J. M.; Ferreira, F.; Ferreira, J. M.; Fang, W.; Falcão, P. F.; Rosa, A. (International Entrepreneurship and Management Journal, 2019)
In an increasingly digital world, almost anything can now be done through a computer or smartphone. Digital entrepreneurship is capitalizing on this trend, which brings numerous advantages to firms and society at large. However, the determinants of digital entrepreneurship’s success are still unclear, as well as how they relate to each other. This study sought to develop a fuzzy cognitive map (FCM) to identify and analyze the determinants of digital entrepreneurship. Two group sessions were held with a panel of decision makers who deal with the digital entrepreneurship phenomenon every day. Based on their shared experience and knowledge, an FCM was developed and validated for this research context. Static and dynamic analyses facilitated a deeper understanding of the cause-and-effect relationships between the determinants of digital entrepreneurship, resulting in a well-informed framework that was validated by the panel members. This methodological procedure enabled an objective analysis of the dynamics behind digital entrepreneurship. The advantages and limitations of our constructivist framework are also discussed.